Data Journalism Practices in Post-Pandemic Hyperlocal Media in Central Sulawesi: A Case Study of Nexteen Media and Tutura.id - Bo'do, Stepanus; Antasari, Citra; Haidar, Nur; Suyatman; Alfarisi, Salman; Agis, Nabila (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This study investigates the transformative practices of data journalism in Indonesian hyperlocal media post-COVID-19, focusing on Nexteen Media and Tutura.id in Central Sulawesi. Through in-depth interviews with editorial leaders, data journalists, and data visualization staff, this study examines the development of these practices. Findings suggest that both outlets leveraged the pandemic to innovate with data-driven reporting. Nexteen Media developed interactive data visualizations to engage younger audiences, while Tutura.id prioritized verified, narrative data reporting to enhance credibility. Both maintained traditional news values, such as geographic proximity and novelty, to attract audience attention. Despite challenges like limited data access and insufficient technical skills, both outlets remain committed to advancing data journalism. This research fills a gap in the literature on data journalism in Indonesian hyperlocal media. Theoretically, it affirms the relevance of traditional news values in the digital era. Practically, it recommends technical skills training and advocacy for open data access to strengthen credibility and impact in local journalism.